Tilbagelænet redskabsmediering – en kulturhistorisk psykologisk rammesætning af biofeedback som helbredsteknologi. - Moesmann, Martin; Mortensen, Ditte Hvad (Psyke & Logos, 2016)
There is a growing demand for tools and methods that provide a setting for the cultivation of conscious focus and immersion. With the intent to accommodate this need, the technology of biofeedback is presented, which has a documented long time effect on the users’ ability to regulate their body states independently. There is, however, little clarity on what kind of psychological dynamics make biofeedback work. To explore a possible theoretical framework, ideas from cultural-historical psychology are presented, with which the phenomenon can be particularly elucidated by the concepts of mediation and interiorization. A design of an interactive chair under development at Bang & Olufsen is presented. The potential for understanding the possible biofeedback properties of the chair and the phenomenon in general within a cultural-historical psychological framework are considered. Future directions for the project and the model are then discussed in light of the presented theory and analysis.